Pengaruh Cita Rasa, Packaging Design, Brand Association, Dan Healthy Lifestyle Terhadap Keputusan Pembelian Cimory Yogurt Squeeze Pada Masyarakat Kebumen - Fitri Anisah; Dewi Noor Susanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The COVID-19 pandemic from 2020 to 2022, which is spreading around the world, has resulted in a transformation in consumer behavior in Indonesia. This transformation includes public awareness of the importance of implementing a healthy lifestyle in choosing foods and drinks that are rich in nutrients to increase endurance. One of the healthy beverage foods that is currently popular is Cimory Yogurt Squeeze. The purpose of this study was to determine the effect of taste, packaging design, brand association, and healthy lifestyle on purchasing decisions for Cimory Yogurt Squeeze in the Kebumen community. This study used a non-probability sampling method with purposive sampling technique conducted on 100 respondents. The data collection technique in this study was to use a questionnaire. The data analysis technique used is multiple linear regression analysis using the SPSS application. The results showed that taste has a significant effect on purchasing decisions, packaging design has an effect on purchasing decisions, brand association has an effect on purchasing decisions, and healthy lifestyle has an effect on purchasing decisions. Simultaneously, taste, packaging design, brand association, and healthy lifestyle have a significant effect on purchasing decisions for Cimory Yogurt Squeeze.